Velamentous Cord Insertion in a Singleton Pregnancy: An Obscure Cause of Emergency Cesarean-A Case Report - Juliana Rocha; Joana Carvalho; Fernanda Costa; Isabel Meireles; Olímpia do Carmo (Hindawi Limited, 2012)
Approximately 2% of low-risk pregnant women still require an emergency Cesarean section after the onset of labor. Because it is likely that half of these cases are associated with placental and umbilical cord abnormalities, it is thought that prenatal detection of such abnormalities would reduce the number of emergency cesarean sections in low-risk women. Velamentous cord insertion is an abnormal cord insertion in which the umbilical vessels diverge as they traverse between the amnion and chorion before reaching the placenta. With a reported incidence of 1% in singleton pregnancies, it has been associated with several obstetric complications. This condition has been diagnosed by ultrasonography with a sensitivity of 67% and specificity of 100% in the second trimester. The present case highlights the importance of the systematic assessment of the placental cord insertion site at routine obstetric ultrasound and the potential of identifying pregnancies with velamentous insertion and, therefore, those at risk for obstetric complications.